Recognition as key for reconciliation : Israel, Palestine, and beyond - Meital, Yoram.; Rayman, Paula M. (Social, Economic and Political Studies of the Middle East and Asia, 2018)
In these times of growing insecurity, widening inequities and deepening crisis for civilized governance, Recognition as Key for Reconciliation offers meaningful and provocative thoughts on how to advance towards a more just and peaceful future. From the intractable Israeli-Palestinian conflict we learn of "thin" and "thick" recipes for solutions. Beyond the Middle East region we learn from studies around the globe: South Africa, Northern Ireland and Armenia show the challenges to genuine recognition of our very human connection to each other, and that this recognition is essential for any sustainable positive security for all of us. Contributors are Deina Abdelkader, Gregory Aftandilian, Dale Eickelman, Amal Jamal, Maya Kahanoff, Herbert Kelman, Yoram Meital, Victoria Montgomery, Paula M. Rayman, Albie Sachs and Nira Yuval-Davis.